MENGEMBANGKAN KEMAMPUAN MENGENAL ANGKA 1-10 MELALUI KARTU ANGKA PADA TAMAN KANAK KANAK KELOMPOK A - Isabella Haslana; Aniek Wirastania (WAHANA, 2017)
Early childhood development is important and needs to be developed especially in education. Oneaspect that needs to be developed in early childhood education is the ability to recognize the conceptof numbers. Therefore, it takes a strategy in learning to introduce the concept of numbers. This studyaims to develop students ability in recognizing the concept of numbers 1-10 by using a number card.The type of research used is quasi experimental design (quasi experiment). The quasi experimentaldesign used in this study is a non-equivalent pretest-posttest control group design. The results of thisstudy were analyzed by the T test conducted using the help of SPSS program. Based on the results ofresearch conducted obtained with sig (0,000) <0.05 which means there is a difference between the experimental group with the control group in recognizing the concept of numbers by using a number card. So it can be concluded that the number cards have an influence in improving the ability torecognize the numbers in children group A.